2021
DOI: 10.1007/s10888-021-09487-6
|View full text |Cite
|
Sign up to set email alerts
|

Which workers bear the burden of social distancing?

Abstract: Using data from O ∗ NET, we construct two measures of an occupation’s potential exposure to social distancing measures: (i) the ability to conduct that job from home and (ii) the degree of physical proximity to others the job requires. After validating these measures with comparable measures from ATUS as well as realized work-from-home rates during the pandemic, we employ the measures to study the characteristics of workers in these types of jobs. Our results show that workers in low-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(101 citation statements)
references
References 20 publications
8
73
0
Order By: Relevance
“…Third, families with low incomes generally experience greater social disruption compared with higher income families because of more unstable work conditions and incomes. 21 , 22 Associations between social disruption and lower SES were only heightened during the pandemic as there were disproportionately larger job losses in sectors where low-income people work such as restaurants, manufacturing, and general blue collar work across countries in our sample. 23 , 24 , 25 As a result of the impacts of social disruption by SES, it has also been shown that these experiences of job loss and income instability, which are now heightened for low-income families, contribute to feelings of stress.…”
Section: Discussionmentioning
confidence: 89%
“…Third, families with low incomes generally experience greater social disruption compared with higher income families because of more unstable work conditions and incomes. 21 , 22 Associations between social disruption and lower SES were only heightened during the pandemic as there were disproportionately larger job losses in sectors where low-income people work such as restaurants, manufacturing, and general blue collar work across countries in our sample. 23 , 24 , 25 As a result of the impacts of social disruption by SES, it has also been shown that these experiences of job loss and income instability, which are now heightened for low-income families, contribute to feelings of stress.…”
Section: Discussionmentioning
confidence: 89%
“…Working from home (WFH) has received growing attention from many scholars over recent years [1,2]. In the pandemic context, many studies have recently examined WFH, particularly from the perspective of identifying those jobs that can be performed remotely [3][4][5][6][7]. In [8], the authors explained that the working from home concept is also known as teleworking.…”
Section: Introductionmentioning
confidence: 99%
“…Occupations that necessitate proximate contact with people perpetuate the risk of infection despite infection prevention efforts, while occupations that promote work from home force employees to undergo rapid changes in their work styles [1][2][3]. These enormous risks and changes in the work environment during the COVID-19 pandemic have increased the physical and mental burden on employees and reduced their well-being [4,5].…”
Section: Introductionmentioning
confidence: 99%